Operation optimization of PLTMG SUMBAGUT 2 peaker 250 MW with homer - M Mahlil; Andik Bintoro (Geuthèë Institute, 2023)
PLTMG SUMBAGUT 2 peaker 250 MW has 13 generator units in parallel so that it is able to provide power of 239 MW, the generating power capacity per engine unit is 18,407 KW, due to the power usage in the load always changing, the P3B must be able to regulate generator operations automatically , economically, every generator operation requires a large amount of financing, especially fuel usage, fuel usage is one of the things that needs special attention because around 60% of the total operating costs incurred are fuel costs, therefore this research aims to Optimizing load and fuel bearing generators in annual plant operations using Lagrange multiplier methodology is simulated in HOMER ENERGI software, the results of this research are a gas engine system consisting of 13 gas engine generators with a capacity of 18407 kW, obtaining optimal generator results at NPC prices (Net Present Cost) is the lowest, HOMER ENERGI software makes simulation calculations easier, the most optimal system design is based on the lowest total NPC of IDR 5,125,319,000,000.00 from 13 generators, only 6 optimal generator units can produce energy of 117,510,454 KWH per year with a Levelized Cost of Energy (Rp/kWh) of 2,040 and consuming 31,274,527 m3/year of fuel.